2022
DOI: 10.3390/diagnostics12061330
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics in Oncological PET Imaging: A Systematic Review—Part 2, Infradiaphragmatic Cancers, Blood Malignancies, Melanoma and Musculoskeletal Cancers

Abstract: The objective of this review was to summarize published radiomics studies dealing with infradiaphragmatic cancers, blood malignancies, melanoma, and musculoskeletal cancers, and assess their quality. PubMed database was searched from January 1990 to February 2022 for articles performing radiomics on PET imaging of at least 1 specified tumor type. Exclusion criteria includd: non-oncological studies; supradiaphragmatic tumors; reviews, comments, cases reports; phantom or animal studies; technical articles withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 174 publications
0
4
0
Order By: Relevance
“…However, in practice, this tool has become the de facto standard for systematic reviews of the literature focused on radiomics quality assessment as confirmed by our findings. In any case, it should be acknowledged that some alternatives have been proposed, even though their use is usually sporadic [66,67]. Additionally, several checklists checklists does not allow a formal methodological quality score, but rather an unweighted assessment of overall adherence to the included items.…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, this tool has become the de facto standard for systematic reviews of the literature focused on radiomics quality assessment as confirmed by our findings. In any case, it should be acknowledged that some alternatives have been proposed, even though their use is usually sporadic [66,67]. Additionally, several checklists checklists does not allow a formal methodological quality score, but rather an unweighted assessment of overall adherence to the included items.…”
Section: Discussionmentioning
confidence: 99%
“…Using mathematical methods, texture analysis evaluates the relationship of pixel density and position within the region of interest and creates secondary parameters that provide a quantitative representation of tumor heterogeneity [10,11]. Several studies have suggested that texture analysis has predictive value in diagnostic imaging in different cancer types [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics, an emerging field of research aiming to extract mineable, quantitative, high-dimensional data from clinical images, has been suggested as a solution [ 12 , 13 , 14 ]. Various studies have explored the possibilities offered by radiomics in HL [ 15 ] whether for computer-aided histological classification [ 16 ], staging [ 17 , 18 ], early metabolic response assessment [ 19 , 20 , 21 ], or refractory disease prediction [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%